The Sufficiency of Vitamin D of the Population of Various Age Groups in the City of Arkhangelsk - S. I. Malyavskaya; I. N. Zakharova; G. N. Kostrova; A. V. Lebedev; Ye. V. Golysheva; I. V. Suranova; I. D. Maykova; Ye. A. Yevseeva (Вопросы современной педиатрии, 2016)
Background: Vitamin D is involved in important physiological processes. Vitamin D deficiency is a risk factor for the formation of various pathological conditions. We are interested in the study of vitamin D sufficiency of the population of various age groups living in the northern regions where the risk of vitamin D deficiency is caused by low insolation.Objective: To evaluate vitamin D sufficiency of the populationof the city of Arkhangelsk in different age groups.Methods: In the prevalence (cross-sectional) uncontrolled study we examined the concentration of 25-OH Vitamin D — 25(OH)D — in the blood serum of residents of both sexes in Arkhangelsk in spring-autumn period 2013–2014. Moderate vitamin D deficiency was determined at the content of 25(OH)D in the range of 20–30 ng/ml, deficiency — at 10–19 ng/ml, severe deficiency — at < 10 ng/ml.Results: The study included children under 3 years (n = 155), school children of 6–7 years (n = 80), adolescents of 13–15 years (n = 184), university students of 18–22 years (n = 88), and adults of 24–60 years old (n = 85). The lack of vitamin D is found in 38 (25%), 16 (20%), 54 (29%), 28 (32%), and 35 (41%); deficiency — in 35 (22%), 39 (49%), 127 (69%), 44 (50%), and 25 (29%); severe deficiency — in 12 (8%), 18 (22%), 1 (1%), 1 (1%), and 3 (4%) of patients, respectively.Conclusion: The high incidence of vitamin D deficiency of varying severity is determined in all age groups of the population living in the city of Arkhangelsk. The findings indicate the necessity of the development and implementation of target regional and national programs for the prevention, early detection, and correction of vitamin D deficiency and associated disorders in the Russian Federation.